Genetic and Phenotypic Association Among Milk Production Traits in Jersey Cattle - DEOKAR, D K; ULMEK, B R (The Indian Journal of Animal Reproduction, 2023)
Milk production is a complex biological phenomenon influenced by both genotype and environment. The information on the interrelationship among the milk production traits is scanty. Therefore, the present study was undertaken to know the association among lactation milk yield (LMY), first 305 days milk yield (F305 DMY), Lactation length (LL) and dry period (DP) in Jersey cattle